(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
In this article, the theory of didactic principles in mathematics lessons, the issue of using other subjects in mathematics lessons, clearly showing in the program, some educational situations of aspects of computer convenience in teaching mathematics, the correct choice of didactic games in preparing for the lesson described in detail.